(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Ductile iron contains free graphite nodules inside of the metallic matrix, which generally consists of ferrite and pearlite in the as-cast condition. The cooling rate has a great influence on the size, shape, and quantity of the microconstituents of the metallic matrix and the graphite nodules and, therefore, on the mechanical properties. In this investigation, the effect of the cooling rate on the metallic matrix and the nodular characteristics of a ductile iron alloyed with low concentrations of Ni and V was studied. The ductile iron was obtained using the sandwich technique with ladle inoculation. Six plates of different thicknesses from 4.3 mm to 25.4 mm were fabricated in a sand mold using a cooling time of 30 minutes. The microstructural characterization was performed by optical microscopy (OM) and scanning electron microscopy (SEM). The quantitative analysis of the graphite nodules and the microconstituents of the metallic matrix was carried out with the Image J software. The mechanical characterization was carried out by the hardness test on the Rockwell C scale. The results show that the decrease in thickness improves the nodular characteristics; In this case, the plate thickness of 4.3 mm obtained the highest nodule count of 414 Nod/mm2, the smallest nodule size (15.30 µm), a space between particles of 18.23 µm, sphericity close to 0 .96 and nodularity of 96.21%. In addition, the highest volume fraction of pearlite (33.7%) and carbides (4.5%) was obtained and consequently the highest hardness (31.56 HRC).